A Study on the Efficacy of Thrombectomy in Patients with Atherosclerotic and Cardioembolic Basilar Artery Occlusion - Chen, Fulei; Dai, Linzhi; Dong, Jiangtao; Zhu, Licang; Li, Yang; Zhang, Lei; Zhao, Dong (Journal of Neurological Surgery Part B: Skull Base, 2023)
Background Studies on basilar artery occlusion are relatively few compared with those of anterior circulation stroke. The aim of the present study was to compare the efficacy of endovascular therapy (EVT) in patients with basilar artery occlusion classified as large artery atherosclerosis (LAA) and cardioembolism (CE), and to analyze the independent risk factors affecting the prognosis of EVT.Methods A total of 123 people were assigned to the LAA and CE groups (97 to the LAA and 26 to the CE). The primary outcome was a modified Rankin Scale (mRS) score of 2 or lower at 90 days. The primary safety outcome was mortality at 90 days. Secondary safety endpoints included the rates of symptomatic intracranial hemorrhage and reinfarction. Multiple logistic regression was used to screen out independent risk factors for EVT prognosis of the LAA and CE groups.Results In the analysis, the patients with LAA stroke had better collateral circulation (American Society of Interventional and Therapeutic Neuroradiology/Society of Interventional Radiology [SIR] score of 2–4; 61.9 vs. 19.2%, p = 0.000), and higher angioplasty rate (32.0 vs. 3.8%, p = 0.002). The proportions of patients with a 90-day mRS score of 0 to 2 and 90-day mortality were not found to be statistically significant between the two groups. Multivariate logistic regression analysis indicated that age, SIR, white blood cell, blood glucose, and modified thrombolysis in cerebral infarction were independent risk factors for the poor prognosis of EVT in the LAA group.Conclusion Although there were differences in clinical characteristics and imaging features between LAA and CE, there was no evidence of a significant difference in prognosis after EVT. In addition, the National Institutes of Health Stroke Scale score was not among the independent risk factors affecting the prognosis of the LAA group.
Keywords: basilar artery occlusion; intravascular therapy; large artery atherosclerosis; cardioembolism